Cell fusions regulation and control - Larsson, Lars-Inge.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Cell fusions are important to fertilization, placentation, development of skeletal muscle and bone, calcium homeostasis and the immune defence system. Additionally, cell fusions participate in tissue repair and may be important to cancer development, progression and therapy. A large number of factors regulate cell fusions, including receptors and ligands, membrane domain organizing proteins, proteases, signaling molecules and fusogenic proteins that bring membranes close together. In the present volume, we interrogate what mechanisms that may be important to cell fusions in mammals and what mechanisms that may be shared with lower organisms and viruses. Additionally, the importance of cell fusions to the pathogenesis as well as treatment of diseases is addressed.
Foreword - Lars-Inge Larsson -- 1 Regulation and control of cell-cell fusions, Lars-Inge Larsson -- 2 Retroviruses and cell fusions: overview, Anders L. Kjeldbjerg, Shervin Bahrami, Finn Skou Pedersen -- 3 Retroviral membrane fusions: regulation by proteolytic processing and cellular factors, Yoshinao Kubo -- 4 A comparative portrait of retroviral fusogens and syncytins, Philippe Pérot, Cécile Montgiraud, Dimitri Lavillette, François Mallet -- 5 Synctins : molecular aspects, Hungwen Chen, Mei-Leng Cheong -- 6 Role of the actin cytoskeleton within FuRMAS during Drosophila myoblast fusions and first functionally conserved factors in vertebrates, Susanne Filiz Önel, Christine Dottermusch, Angela Sickmann, Detlev Buttgereit, Renate Renkawitz-Pohl -- 7 Role of CD9 in sperm-egg fusion and its general role in fusion phenomena, Natsuko Kawano, Yuichiro Harada, Keiichi Yoshida, Mami Miyado, Kenji Miyado -- 8 Gemate binding and fusion, Young-Joo Yi, Shawn W. Zimmerman, Peter Sutovsky -- 9 Mechanisms regulating human trophoblast fusion, Berthold Huppertz, Martin Gauster -- 10 Macrophage fusion: the making of a new cell, Agnès Vignery -- 11 Molecules regulating macrophage fusions, Takeshi Miyamoto, Toshio Suda -- 12 Current progress towards understanding mechanisms of myoblast fusion in mammals, Grace K. Pavlath -- 13 The endogenous envelop protein synctin is involved in myoblast fusion, Bolette Bjerregaard, Jan Fredrik Talts, Lars-Inge Larsson -- 14 Cell Fusion and stem cells, Alain Silk, Anne E. Powell, Paige S. Davies, Melissa H. Wong -- 15 Cell Fusion and dendritic cell-based vaccines, Jianlin Gong, Shigeo Koido -- 16 Cancer cell fusion with myeloid cells: implications for energy metabolism in malignant hybrids, Rossitza Lazova, Ashok K. Chakraborty, John M. Pawelek -- 17 Cell-cell fusions and human endogenous retroviruses in cancer, Reiner Strick, Matthias W. Beckmann, Pamela L. Strissel -- Index.
Electronic reproduction.
Keywords: Cell hybridization; Cell Fusion; Cytogenetics; Electronic books